Evaluation of Anti-SARS-CoV-2 IgG Responses in a Clinical Study of a Biosimilar Candidate to Denosumab Using Singlicate Analysis - Sandra Ribes; Natalia Krivtsova; Celine Schelcher; Ana Villalba-Izquierdo; Falko Reiss; Mandy Richter; Katrin Reisinger; Johann Poetzl (Drugs in R&D)
Abstract Background and Objectives During the coronavirus disease-2019 (COVID-19) pandemic there was the uncertainty that the long-term immune response generated upon natural infection or triggered by available severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) vaccines could impact the clinical endpoints of ongoing clinical trials, in particular, whether the immunogenicity of biotherapeutics could be affected. Methods Here, we describe the different stages to build an adequate COVID-19 serology testing strategy to ultimately assess whether the presence of anti-SARS-CoV-2 antibodies could impact the immunogenicity data of a clinical trial supporting the approval of GP2411 (Jubbonti®/Wyost®; a denosumab biosimilar to Prolia/XGeva) conducted during the pandemic. We first assessed the sensitivity and specificity of US Food and Drug Administration Emergency Use Authorization (FDA EUA)-approved commercial SARS‐CoV‐2 anti‐IgG enzyme-linked immunosorbent (ELISA) assay. Then, we validated the assay in accordance with bioanalytical guidelines and demonstrated that the analysis of validation parameters as singlicates met all bioanalytical acceptance criteria and showed comparable results to those of duplicate analyses. Lastly, we report data on anti-SARS-CoV-2 IgG antibody responses in healthy participants treated with a single dose of a biotherapeutic. Results SARS-CoV-2 serology was assessed in 1970 serum samples collected from 499 healthy participants who were dosed throughout a clinical study that was conducted during the COVID-19 pandemic. Anti-SARS-CoV-2 IgG antibodies triggered by natural infection and/or vaccination were detected in 1165 serum samples from 82% of the study participants. Anti-SARS-COV-2 IgG responses were of comparable magnitude in study participants who were vaccinated during the course of the study or had a confirmed COVID-19 infection. A total of 6408 serum samples from the same study were evaluated for the presence of anti-drug antibodies (ADAs), with 64% of the participants being positive. Independent of the presence of anti-SARS-CoV-2 IgG antibodies, all ADA-positive study participants showed ADAs of very low magnitude. Neutralizing ADAs were detected in less than 1% of study participants without an association to anti-SARS-CoV-2 IgG responses. Conclusions The established bioanalytical strategy allowed the reliable detection of COVID-19 adaptive responses in study participants. The development of anti-SARS-CoV-2 IgG responses (triggered by either a natural infection or a vaccine) did not have any clinically meaningful impact on the immunogenicity of the biotherapeutic administered in the study.